Religion: spiritual health guide - Mahdi Fani; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Spirituality and spiritual health terms were not used in the era of the emergence of Quran and Hadiths of Ahl al-Bayt, but today they have been applied in various areas of science, especially medical sciences. Therefore the aim of this study is determination of spiritual health scope conceptually based on the concept of "religion" and "health" used in the Quran and Hadiths, and the effect of religion is partly revealed in this type of health. Results showed spiritual health should be searched in having the correct faith and belief, Divine morality and piety. Although, according to conducted research, spiritual health can also be effective in human body health. Keywords:Religion, Health, Spirituality For downloading the full-text of this article please click here.